PERBEDAAN RADIOPASITAS ANTARA SEALER BERBAHAN DASAR RESIN EPOKSI DAN SEALER BERBAHAN DASAR SENG OKSID EUGENOL DENGAN TEKNIK RADIOGRAFI PERIAPIKAL DIGITAL - , HANNA LIZA UTAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Radiopacity is the inability of X-rays to penetrate material that causes radiopaque. Sealer, along with gutta percha, is used as a root canal filling material. Then, obturation process of the root canal treatment was evaluated by radiograph. Therefore, the sealer must be radiopaque to difference with anatomy structure in the radiograph. The aim of this study was to determine the difference of radiopacity between epoxy resin based sealer compared with zinc oxide eugenol based sealer on digital periapical radiography techniques. Twenty sealer study samples were divided into two groups. Group I consisted of 10 samples of epoxy resin based sealer . Group II consisted of 10 samples of zinc oxide eugenol based sealer. Images were taken from both groups by using radiograph technique with periapical digital radiographic techniques with the specification of 50 kVp, 7mA , and 0.8 seconds. Observations were carried out using the Image J software. The results of calculations were analyzed by using the Independent t - test. The results showed that significant radiopacity differences were occurred in both groups (p < 0.05). Epoxy resin based sealer (6,85 mmAl) was significantly more radiopaque than zinc oxide eugenol based sealer (3,22 mmAl). Radiopacity was influenced of chemical composition, inorganic contrast medium, atom number, and the density of the sealer. The conclusion of this study is that epoxy resin based sealer is more radiopaque than zinc oxide eugenol based sealer. Keywords: radiopacity, sealer, radiography, periapical, digital.